A high-precision and high-performance brush material for micro motor and its preparation method
Through the continuous press-rolling and heat-combining technology of zinc-white copper layer and AgPdCuPtRE alloy layer, the domestic brush materials are solved in the high-end market, and the high-precision and high-performance brush materials are achieved, reducing external dependence.
Patent Information
- Application Number
- CN202411204213.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-30
- Publication Date
- 2025-03-14
- Estimated Expiration
- 2044-08-30
AI Technical Summary
The positioning accuracy and thickness control of domestic micromotor brush materials in the high-end market is difficult to reach the international advanced level, resulting in a high degree of dependence on foreign countries.
The continuous press-rolling and heat-composite technology of zinc-white copper layer and AgPdCuPtRE alloy layer is used to prepare high-precision and high-performance brush materials through specific component ratios and process parameters.
The accuracy and performance of the brush material are achieved, and the thickness accuracy is controlled at ±0.002mm, which extends the service life of the brush material and reduces the dependence on the outside.
Smart Images

Figure CN118738967B_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of micro motor brush materials, and more specifically, to a high-precision and high-performance brush material for a micro motor and a preparation method thereof. Background Art
[0002] In recent years, domestic micromotor technology has developed rapidly. With the further improvement of micromotor electromagnetic field theory, its information technology, material technology, and micromotor process technology have all been significantly innovated and improved, taking the micromotor motor for new energy vehicles as an example.
[0003] At this stage, automotive micromotors can effectively meet the technical application needs of active safety, intelligence, comfort, etc. proposed by automobile manufacturers due to their lightweight, high efficiency, low noise and intelligence. The market size of a single product accounts for about 15% of the total micromotor market size.
[0004] However, the micromotor industry is a technology-intensive industry, and the performance and precision requirements of the brush materials of its core components are extremely stringent. The manufacturers of this material are mainly concentrated in Japan's Tanaka and South Korea's Changxing. Its positioning accuracy usually fluctuates below 0.2mm, the thinnest thickness can be 0.03mm, the accuracy is controlled within ±0.003mm, and it has a long brush life.
[0005] In recent years, although domestic brush materials have developed rapidly, they are still in the middle and low-end market, and their high-end market dependence on foreign countries is still relatively high, because their positioning accuracy fluctuates greatly, usually fluctuating below 0.5mm, and when the thickness is below 0.05mm, the corresponding performance cannot be retained. In summary, a high-precision and high-performance brush material for micromotors suitable for the high-end market and capable of achieving both performance and accuracy and a preparation method thereof are provided. Summary of the invention
[0006] In order to achieve a balance between performance and precision, and thus realize domestic substitution in the high-end market, the present application specifically provides a high-precision and high-performance brush material for a micromotor and a preparation method thereof.
[0007] In the first aspect, the present application provides a high-precision and high-performance brush material for a micromotor, which adopts the following technical solution:
[0008] A high-precision and high-performance brush material for micromotors, which is made of a zinc-nickel copper layer and an AgPdCuPtRE alloy layer by continuous pressing and hot-rolling;
[0009] The thickness ratio of the zinc-white copper layer to the AgPdCuPtRE alloy layer is 1:(0.05-0.3);
[0010] The AgPdCuPtRE alloy layer is composed of the following components in mass percentage: 0-0.5% RE, 20-40% Pd, 20-40% Cu, 0.2-1% Pt, and the balance is Ag.
[0011] Preferably, the zinc-white copper layer is composed of the following components in percentage by mass:
[0012] 17.5-18.5% Zn, 25.5-26.5% Ni, 0.5-0.8% RE, balance Cu.
[0013] Preferably, the RE consists of Y and Pr in a weight ratio of 1:(0.3-0.5).
[0014] In a second aspect, the present application provides a high-precision and high-performance brush material for a micromotor and a preparation method thereof, comprising the following steps:
[0015] S1. The AgPdCuPtRE alloy layer and the zinc-nickel copper layer are continuously pressed and hot-compounded under a protective atmosphere to obtain a AgPdCuPtRE alloy / zinc-nickel copper composite material;
[0016] S2, performing diffusion annealing on the composite material obtained in S1 under a protective atmosphere;
[0017] S3, performing pickling treatment on the composite material after diffusion annealing in S2;
[0018] S4, cold rolling the AgPdCuPtRE alloy / zinc-white copper composite material after pickling treatment in S3, the rolling deformation of the billet is controlled at 30-70%, and the deformation of each processing does not exceed 30%;
[0019] S5, performing intermediate heat treatment on the composite material after cold rolling in S4 under a protective atmosphere;
[0020] S6, rolling the AgPdCuPtRE alloy / zinc-white copper composite material after annealing in S5 into finished product, controlling the rolling deformation to be 30-70%, and the deformation of each processing not exceeding 30%, until the finished product thickness is obtained, and then performing surface degreasing treatment to remove surface oil stains;
[0021] S7, the surface-treated AgPdCuPtRE alloy / zinc-nickel-copper finished product in S6 is striped and cut to a corresponding width, and then subjected to low-temperature aging treatment under a protective atmosphere;
[0022] S8. Correct the plate shape of the AgPdCuPtRE alloy / nickel white copper product obtained in S7, control the lateral bending to ≤3mm / m, and then inspect, roll up, wind with weather paper and vacuum pack, so as to obtain a high-precision and high-performance brush material for micro motors.
[0023] Preferably, the flow rate of the protective atmosphere is:
[0024] Ammonia decomposition gas 1-5 m 3 / h, nitrogen 1-4 m 3 / h.
[0025] Preferably, the process conditions of S1 are as follows:
[0026] The continuous pressing and hot-compounding process controls the total deformation of the AgPdCuPtRE alloy / zinc-nickel-copper composite material to be 30-65%, and the composite parameters are: temperature 400-700℃, speed 1.0-5.0m / min.
[0027] Preferably, the process parameters of the diffusion annealing in S2 are: annealing temperature 500-800° C., annealing speed 1.0-5.0 m / min.
[0028] Preferably, the pickling treatment in S3 uses a dilute sulfuric acid aqueous solution with a mass concentration of 5-25%, and the pH value of the hot water tank is controlled to be 5-8.
[0029] Preferably, the process parameters of the intermediate heat treatment in S5 are: annealing temperature 500-800° C., annealing speed 1.0-5.0 m / min.
[0030] Preferably, the process parameters of the low temperature aging treatment in S7 are: annealing temperature 300° C.-400° C., annealing speed 1.0-5.0 m / min.
[0031] In summary, this application has the following beneficial effects:
[0032] 1. The AgPdCuPtRE alloy layer of the present application has a strengthening effect on its metallographic structure and its material itself by adding alloying elements such as Cu, Pt, and rare earth, thereby significantly improving its hardness and ductility. After being compounded with the zinc-white copper layer, it can achieve a balance between precision and performance;
[0033] 2. The zinc-white copper layer composed of specific elements in the present application, after being compounded with the AgPdCuPtRE alloy layer, can not only effectively ensure the bonding between the two, but also endow the material with excellent resilience and conductivity through the synergy of the layer structure, which is beneficial to prolong the service life of the brush material;
[0034] 3. The composite process in the related technology requires surface treatment of the substrate to reduce the zinc volatilization phenomenon caused by the temperature above 600°C, and then ensure the composite fastness and the stability of the brush material process, but the surface treatment additives used will still have a large load on the environment;
[0035] Therefore, the present application specially achieves the replacement of the process by adjusting the formula, that is, by means of rare earth element RE, as well as specific selection and compounding, specifically: Y and Pr are composed in a weight ratio of 1: (0.3-0.5), thereby improving the metallographic phase, composition and structure of the contact surface and reducing the volatilization of zinc;
[0036] 4. The continuous rolling hot composite process adopted in this application ensures the thickness uniformity of the silver-palladium alloy and the zinc-white copper alloy after composite by controlling the process parameters such as the pressing deformation amount, heating temperature, belt speed, and sufficient recrystallization annealing. The final product thickness is 0.02 to 0.04mm, the thinnest silver-palladium alloy can be 0.001mm, and the thickness accuracy is controlled at ±0.002mm. BRIEF DESCRIPTION OF THE DRAWINGS
[0037] Figure 1 This is a microscopic metallographic structure picture of the high-precision and high-performance brush material for the micromotor in Example 1 - horizontal;
[0038] Figure 2 This is a microscopic metallographic structure picture of the high-precision and high-performance brush material for micro motors in Example 1 - longitudinal direction;
[0039] Figure 3 This is a microstructure picture of the brush material for the micromotor in Comparative Example 1 - horizontal;
[0040] Figure 4 This is a microstructure picture of the brush material for the micromotor in Comparative Example 1 - longitudinal. DETAILED DESCRIPTION
[0041] The following is combined with Figure 1-4 The present application is further described in detail with reference to the accompanying drawings and embodiments.
[0042] Performance test: The brush materials for micro motors prepared in the embodiments and comparative examples were selected to test their accuracy, hardness, resilience and service life. The specific testing steps are as follows:
[0043] Precision measurement: The brush material for micro motors is produced according to the specification of 0.03mm, and then its thickness deviation is measured by a screw micrometer. After 10 groups of parallel tests, the average value is taken and recorded in the table below.
[0044] Hardness measurement: The Vickers hardness HV of the brush material for the micromotor is tested by a microhardness tester of model HXD-1000TMC LCD (measuring the precious metal surface of the AgPdCuPtRE alloy layer). After 10 groups are tested in parallel, the average value is taken and recorded in the following table.
[0045] Rebound force: The rebound force of the brush material for the micromotor is tested by a fully automatic load displacement testing machine of model 1305R. After 10 groups of parallel tests, the average value is taken and recorded in the following table.
[0046] Service life measurement: characterized by wear rate (μm / 100h), using commercially available DC vacuum cleaner motor R545-130A (DC21.6V / 130W) as the test motor for brush life comparison; using a DC voltage and current stabilized power supply load endurance test controller to test the prepared brush material.
[0047] Embodiment 1-5:
[0048] A high-precision and high-performance brush material for micromotors, which is formed by continuous pressing and hot-rolling of a zinc-nickel copper layer and an AgPdCuPtRE alloy layer at a thickness ratio of 1:0.05;
[0049] The weights of the components of the zinc-white copper layer and the AgPdCuPtRE alloy layer (calculated per 100 kg) are shown in the following table, and are prepared by the following continuous pressing and hot compounding process:
[0050] S1. Under a protective atmosphere, the AgPdCuPtRE alloy substrate and the zinc-nickel-copper substrate are continuously pressed and hot-compounded to obtain a AgPdCuPtRE alloy / zinc-nickel-copper composite material;
[0051] The flow rate of protective atmosphere is: ammonia decomposition gas 3 m 3 / h, nitrogen 2 m 3 / h;
[0052] The continuous pressing and hot-compounding process controls the total deformation of the AgPdCuPtRE alloy / zinc-nickel-copper composite material at 65%, and the composite parameters are: temperature 700℃, speed 5.0m / min.
[0053] S2, performing diffusion annealing on the composite material obtained in S1 under a protective atmosphere, the annealing parameters are: annealing temperature 600°C, annealing speed 5.0 m / min;
[0054] The flow rate of protective atmosphere is: ammonia decomposition gas 3 m 3 / h, nitrogen 1 m 3 / h.
[0055] S3. The composite material after diffusion annealing in S2 is pickled. The pickling treatment uses a dilute sulfuric acid aqueous solution with a mass concentration of 5%, and the pH value of the hot water tank is controlled to be 6.0.
[0056] S4, cold rolling the AgPdCuPtRE alloy / zinc white copper composite material after pickling treatment in S3, the rolling deformation of the billet is controlled at 50%, and the deformation of each processing does not exceed 30%;
[0057] S5. Performing intermediate heat treatment on the cold-rolled composite material in S4 under a protective atmosphere. The process parameters of the intermediate heat treatment are: annealing temperature 600° C., annealing speed 3.0 m / min.
[0058] S6. The AgPdCuPtRE alloy / zinc-nickel-copper composite material annealed in S5 is rolled into finished product, and the rolling deformation is controlled at 50%, and the deformation of each processing does not exceed 30% until the finished product thickness is obtained, and then the surface is degreased to remove surface oil stains.
[0059] S7, the surface-treated AgPdCuPtRE alloy / zinc-nickel-copper finished product in S6 is striped and cut to a corresponding width, and then subjected to low-temperature aging treatment under a protective atmosphere;
[0060] The flow rate of protective atmosphere is: ammonia decomposition gas 5 m 3 / h, nitrogen 3 m 3 / h, the process parameters of low temperature aging treatment are: annealing temperature 300℃, annealing speed 1.0m / min.
[0061] S8. Correct the plate shape of the AgPdCuPtRE alloy / nickel white copper product obtained in S7, control the lateral bending to ≤3mm / m, and then inspect, roll up, wind with weather paper and vacuum pack, so as to obtain a high-precision and high-performance brush material for micro motors.
[0062] Table: Components and dosage of zinc-nickel-copper layer in Examples 1-5 (kg)
[0063]
[0064] Table: AgPdCuPtRE alloy layer components and their amounts in Examples 1-5 (kg)
[0065]
[0066] RE is composed of Y and Pr in a weight ratio of 1:0.3.
[0067] Comparative Example 1
[0068] A brush material for micromotors was purchased from the Tanaka Precious Metals Group of Japan. The brand name is SP-3 and the thickness is 0.03mm. The accuracy is poor because the finished product purchased was verified by the manufacturer and the rough product after production could not be obtained and tested, so the actual accuracy may be worse.
[0069] The brush materials for micro motors prepared in the above-mentioned Examples 1-5 and Comparative Example 1 were sampled, and then their accuracy, hardness, resilience and service life were tested respectively, and the average values were recorded in the following table.
[0070] Table: Performance test results of Examples 1-5 and Comparative Example 1
[0071]
[0072] It can be seen from the above table that the brush materials for micro motors prepared in Examples 1-5 have excellent precision, Vickers hardness, resilience and service life, and are suitable for the high-end market while being able to achieve both performance and precision. The minimum precision is 0.003mm, and the Vickers hardness is 280-320kgf / mm 2 , the resilience is as high as 630-641μm, and the wear rate is only 2.62-2.85μm / 100h;
[0073] Combined with the data of Examples 1-5 and Comparative Example 1 in the above table, and Figure 1-4 It can be seen that the performance of the present application has achieved domestic substitution of comparative example 1, and the reasons are analyzed as follows:
[0074] 1) In terms of precision, thanks to the addition of alloying elements such as Cu, Pt, and rare earth in the AgPdCuPtRE alloy layer, the material is endowed with better ductility, thereby achieving relative control of precision, but the precision is more easily affected by the Zn content of the zinc white copper layer, refer to Examples 2, 4-5;
[0075] 2) In terms of hardness, the addition of alloying elements such as Cu, Pt, and rare earth can effectively improve the uniformity of the structure of the silver alloy and strengthen the alloy matrix. Specifically, the recrystallization temperature is increased by rare earth elements and their compounds, which can effectively delay the decrease in hardness of cold-deformed silver materials after failure.
[0076] 3) In terms of resilience, since the main material that imparts the resilience is the zinc-nickel copper layer, the performance fluctuations of Examples 1-5 are small. In other embodiments, the zinc-nickel copper layer may be replaced with other materials with similar components and / or proportions, which should not be regarded as a limitation to the present application;
[0077] 4) In terms of service life, thanks to the excellent hardness of the AgPdCuPtRE alloy layer, its wear rate is only 2.72-3.11μm / 100h. Especially after adding rare earth, its wear rate can be further reduced to a minimum of 2.72μm / 100h, refer to Examples 2-5.
[0078] In summary, the zinc-white copper layer composed of specific elements in the present application, after being compounded with the AgPdCuPtRE alloy layer, can not only effectively ensure the bonding between the two, but also endow the material with excellent resilience and conductivity through the synergy of the layer structure, which is beneficial to prolonging the service life of the brush material;
[0079] In addition, the continuous rolling hot composite process adopted in this application ensures the thickness uniformity of the silver-palladium alloy and the zinc-white copper alloy after composite by controlling the process parameters such as the pressing deformation, heating temperature, belt speed, and sufficient recrystallization annealing. The thickness of the final product is 0.02 to 0.04mm, and the thinnest silver-palladium alloy can be 0.001mm, and the thickness accuracy is controlled within ±0.002mm. Therefore, the composite material is applied to the brush of the micro motor to enable it to operate more stably and efficiently.
[0080] Embodiment 6-10:
[0081] A high-precision and high-performance brush material for a micromotor, which is different from Example 2 in that only the components and amounts of the zinc white copper layer are shown in the following table, and the components and amounts of the AgPdCuPtRE alloy layer and the preparation process are the same as those in Example 2;
[0082] Table: Components and dosage of zinc-nickel-copper layer in Examples 6-10 (kg)
[0083]
[0084] RE is composed of Y and Pr in a weight ratio of 1:0.3.
[0085] The brush materials for micro motors prepared in the above-mentioned embodiments 6-10 were sampled, and then their accuracy, hardness, resilience and service life were tested respectively, and the average values were recorded in the following table.
[0086] Table: Performance test results of Examples 6-10
[0087]
[0088] It can be seen from the above table that the brush materials for micro motors prepared in Examples 6-10 all have excellent precision, hardness, resilience and service life. The precision is only 0.001mm, the Vickers hardness is 286-288kgf / mm², the resilience is as high as 870-972μm, and the wear rate is 2.74-2.77μm / 100h;
[0089] It can be seen that the performance is improved to varying degrees compared with Example 2, and the reasons are analyzed as follows:
[0090] 1) In terms of precision, thanks to the addition of rare earth elements in a special ratio in zinc-nickel-copper alloy and the adjustment of the process, this application effectively reduces the volatilization of zinc during the heating process by improving the metallographic phase, composition and structure of the contact surface, thereby ensuring the composite fastness and the precision of the brush material process;
[0091] 2) In terms of hardness, since the test was done on the AgPdCuPtRE alloy layer, there was basically no change. The small fluctuation was speculated to be that a small amount of rare earth elements were transferred from the zinc-nickel alloy to the AgPdCuPtRE alloy layer during the composite process, thereby strengthening the hardness of the AgPdCuPtRE alloy layer;
[0092] 3) In terms of resilience, compared with Example 2 without rare earth elements, its performance is significantly improved because the added rare earth elements can refine the grains, improve the microstructure of the alloy, and promote the uniform distribution of the second phase in the alloy. The fine grain structure and the uniformly distributed second phase can improve the strength and hardness of the alloy, reduce plastic deformation, and thus improve the resilience.
[0093] Alloys with high resilience have advantages in forming, stamping, bending and other processes. They can reduce the springback error of parts, improve processing accuracy and the quality of brush materials. They are the core improvement point of automotive micromotors at this stage, and there is no precedent for improving them in existing products.
[0094] 4) In terms of service life, thanks to the change in the hardness of the AgPdCuPtRE alloy layer in some groups, its wear rate also changes accordingly. Referring to Examples 7-10, its wear rate is inversely proportional to the hardness of the alloy layer. The greater the hardness, the lower the wear rate and the higher the service life.
[0095] Embodiment 11-15:
[0096] A high-precision and high-performance brush material for a micromotor, which is different from Example 7 in that the selection and proportion of RE used in the zinc-white copper layer are different, and the specific corresponding relationship is shown in the following table.
[0097] Table: Selection and ratio comparison table of RE in Examples 11-15
[0098]
[0099] The brush materials for micro motors prepared in the above Examples 11-15 were sampled, and then their accuracy, hardness, resilience and service life were tested respectively, and the average values were recorded in the following table.
[0100] Table: Performance test results of Examples 11-15
[0101]
[0102] It can be seen from the above table that the brush materials for micro motors prepared in Examples 11-15 all have excellent precision, hardness, resilience and service life, with a precision of 0.001-0.003mm, a Vickers hardness of 288kgf / mm², a resilience of up to 821-982μm, and a wear rate of 2.76μm / 100h;
[0103] Combined with Examples 7, 11-15, the performance changes and reasons are analyzed as follows:
[0104] 1) In terms of precision, thanks to the addition of rare earth elements in a special ratio in zinc-nickel-copper alloy and the adjustment of the process, this application can reduce the volatilization of zinc during the heating process to a certain extent by improving the metallographic phase, composition and structure of the contact surface, thereby ensuring the composite fastness and the precision of the brush material process;
[0105] 3) In terms of resilience, compared with Example 2 without rare earth element addition, its performance is significantly improved, and it can be concluded that the RE is preferably composed of Y and Pr in a weight ratio of 1: (0.3-0.5). Although other rare earths also have corresponding effects, they are not compatible with precision and resilience, refer to Examples 11-12;
[0106] As for the hardness and service life, since only the AgPdCuPtRE alloy layer was tested and the components and proportions thereof were unchanged in Examples 11-15, the performance thereof was also basically unchanged.
[0107] In summary, the introduction of rare earth in this application effectively replaces the surface treatment of the substrate required in the traditional composite process, and can also reduce the zinc volatilization phenomenon caused by temperatures above 600°C, thereby ensuring the composite fastness and the accuracy of the brush material process without the need for additional surface treatment additives.
[0108] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.
Claims
1. A high-precision and high-performance brush material for a micromotor, characterized in that: It is formed by continuous pressing and hot-compounding of zinc-nickel copper layer and AgPdCuPtRE alloy layer; The thickness ratio of the zinc-white copper layer to the AgPdCuPtRE alloy layer is 1:(0.05-0.3); The AgPdCuPtRE alloy layer is composed of the following components in mass percentage: 0-0.5% RE, 20-40% Pd, 20-40% Cu, 0.2-1% Pt, and the balance is Ag; The zinc-white copper layer is composed of the following components in percentage by mass: 5-18.5% Zn, 25.5-26.5% Ni, 0.5-0.8% RE, balance Cu; The RE in the zinc white copper layer is composed of Y and Pr in a weight ratio of 1:(0.3-0.5).
2. The method for preparing the high-precision and high-performance brush material for micro-motor according to claim 1, characterized in that: The following steps are involved: S1. The AgPdCuPtRE alloy layer and the zinc-nickel copper layer are continuously pressed and hot-compounded under a protective atmosphere to obtain a AgPdCuPtRE alloy / zinc-nickel copper composite material; S2, performing diffusion annealing on the composite material obtained in S1 under a protective atmosphere; S3, performing pickling treatment on the composite material after diffusion annealing in S2; S4, cold rolling the AgPdCuPtRE alloy / zinc-white copper composite material after pickling treatment in S3, the rolling deformation of the billet is controlled at 30-70%, and the deformation of each processing does not exceed 30%; S5, performing intermediate heat treatment on the composite material after cold rolling in S4 under a protective atmosphere; S6, rolling the AgPdCuPtRE alloy / zinc-white copper composite material after annealing in S5 into finished product, controlling the rolling deformation to be 30-70%, and the deformation of each processing not exceeding 30%, until the finished product thickness is obtained, and then performing surface degreasing treatment to remove surface oil stains; S7, the surface-treated AgPdCuPtRE alloy / zinc-nickel-copper finished product in S6 is striped and cut to a corresponding width, and then subjected to low-temperature aging treatment under a protective atmosphere; S8. Correct the plate shape of the AgPdCuPtRE alloy / nickel white copper product obtained in S7, control the lateral bending to ≤3mm / m, and then inspect, roll up, wind with weather paper and vacuum pack, so as to obtain a high-precision and high-performance brush material for micro motors.
3. The method for preparing the high-precision and high-performance brush material for micro motors according to claim 2, characterized in that: The flow rate of protective atmosphere is: Ammonia decomposition gas 1-5 m 3 / h, nitrogen 1-4 m 3 / h.
4. The method for preparing the high-precision and high-performance brush material for micro-motor according to claim 2, characterized in that: The process conditions of S1 are as follows: The continuous pressing and hot-compounding process controls the total deformation of the AgPdCuPtRE alloy / zinc-nickel-copper composite material to be 30-65%, and the composite parameters are: temperature 400-700℃, speed 1.0-5.0m / min.
5. The method for preparing the high-precision and high-performance brush material for micro motors according to claim 2, characterized in that: The process parameters of the diffusion annealing in S2 are: annealing temperature 500-800° C., annealing speed 1.0-5.0 m / min.
6. The method for preparing the high-precision and high-performance brush material for micro motors according to claim 2, characterized in that: The pickling treatment in S3 uses a dilute sulfuric acid aqueous solution with a mass concentration of 5-25%, and the pH value of the hot water tank is controlled to be 5-8.
7. The method for preparing the high-precision and high-performance brush material for micro-motor according to claim 2, characterized in that: The process parameters of the intermediate heat treatment in S5 are: annealing temperature 500-800° C., annealing speed 1.0-5.0 m / min.
8. The method for preparing the high-precision and high-performance brush material for micro motors according to claim 2, characterized in that: The process parameters of low temperature aging treatment in S7 are: annealing temperature 300℃-400℃, annealing speed 1.0-5.0m / min.
Citation Information
Patent Citations
Pt-containing slide contact material and layered composite material
CN102747247A
High-performance alloy material and strap-shape composite material for micromotor electric bush and producing method thereof
CN105296787A